Pengujian validitas dan reliabilitas Skala Dukungan Iman - Suwartono, Christiany; Suhendra, Junianawaty; Soeherman, Sylvia; Mamahit, Aileen P. (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2019)
The formation of faith in adolescents and young people is rooted in their interaction with parents, both father, and mother, as well as friends. Adolescence and young adulthood are periods of seeking faith in various aspects of life. However, there has not been a measurement of the extent to which adolescents and young people regard parents and friends as role models of their faith. This study was aimed to the Perceived Faith Support - Parents and Friends Scale to be the Scale of Faith Support. The study was conducted through convenience sampling, involving 1,390 participants from three major islands in Indonesia. The results of this adaptation proved to be reliable with internal consistency methods, especially Cronbach's Alpha and to be valid with factor analysis methods. Validation with age criteria is proven by the support of faith from the father and mother, but not with friends. The Faith Support Scale is argued to be fit for both theoretical and practical purposes. The development and application of this scale are further discussed.